Affirmative action policy on women's representation in elections: A study of Hannah Arendt's contemporary thought - Carissa Diva Triandita; Vanya Aisya; Ahmad Mujahid Arrozy (Privietlab, 2026)
The affirmative action policy mandating a 30 percent quotafor female legislative candidates in Indonesia aims to addressgender inequality in politics and expand women’sparticipation in the public sphere. However, women’srepresentation in parliament remains below the expectedtarget. This study analyzes the effectiveness of the policy in enhancing women’s political representation using a descriptive qualitative approach. Data were collected throughliterature review from secondary sources such as academicjournals, government reports, and relevant internationalpublications. The analysis applies Hannah Arendt’s politicaltheory, emphasizing political action and pluralism in thepublic sphere. The findings reveal that the affirmative actionpolicy has achieved only formal, not substantive, representation. Major obstacles include patriarchal culture, male dominance in political parties, and limited institutionalsupport for female candidates. Nevertheless, the policy has positively influenced women’s political participation and thecreation of more gender-responsive public policies. Therefore, strengthening women’s Keywords: affirmative action, women’s quota, politicalrepresentation, Hannah Arendt feminism, patriarchy